Editorial special issue on genomic assisted crop improvement - Kim, Sung-Ryul; Jeon, Jong-Seong; Chin, Joong Hyoun (Elsevier, 2024)
Genomics has a great potential to improve agronomical traits of crop plants to deal with the future needs of a growing human population. Many genomics assisted new tools, such as development of molecular marker and identification of novel genes associated with phosphorus use/acquisition efficiency, enables scientists to efficiently engineer novel traits and precisely edit genomic targets to improve crop plants. This special issue covers research and review articles exploiting genomics assisted research for crop improvement. The Special Issues: “Genomic assisted crop improvement” (https://www.sciencedirect.com/journal/current-plant-biology/special-issue/10LQZ50TVGV) includes seven articles on various crops. A key summary and its various applications are summarized as follows.